Evaluation of the 3D technology in the auto-transplantation: An original research - Shiwangi Singh; Ekta Gupta; I Nalini Sailaja; Bharathiram Guduri; Abhishekh Kumar; Shivaji R Uddarraju; Rahul Tiwari (Wolters Kluwer Medknow Publications, 2024)
Introduction: Using three-dimensional printed duplicates of the donor teeth, three-dimensional auto-transplantation is a medical procedure that moves a tooth from one location inside a patient to another. The intraoperative practicability during 3D auto-transplantation of teeth was evaluated in the present study. Material and Methods: A prospective multicenter clinical study was done among the subjects. "Preoperative cone-beam computed tomography imaging," "computer-assisted design (CAD)," and "computer-assisted manufacturing (CAM)" were used in all operations to make a 3D duplicate of the donor teeth. The clinical parameters that were evaluated were the time required for the fit, number of attempts to fit, and intra-operative experience. Results: Canines, premolars, molars, and one extra tooth were all transplanted during the 200 auto-transplantation surgeries among 152 subjects. An initial satisfactory fit of the donor tooth and an extra-alveolar time of less than one minute were achieved in 80% of the surgeries. The extra-alveolar time exceeded 3 minutes in ten teeth. Difficulties that were faced were related to the imaging, patient cooperation, and the bone quality. Conclusions: The application of the duplicate teeth by 3D printing of a donor tooth all through auto-transplantation techniques reduced the time the tooth stays extra-alveolar as well as the efforts at transplant fitting during implantation. This allowed for more challenging surgeries as well as a speedy and reliable therapy.